Стратегия государственного регулирования земель сельскохозяйственного пользования в Украине - Абдураимова, Э.Д. (Культура народов Причерноморья, 2013)
В статье обоснована необходимость разработки единого документа, который бы отражал государственную политику в сфере эффективного землепользования, систематизировал и взаимоувязывал существующие законодательные акты в сфере земельных отношений. В результате исследования разработаны основные направления стратегии эффективного использования сельскохозяйственных земель. Стратегия государственного регулирования земель сельскохозяйственного пользования представляет собой совокупность организационного, финансово- экономического и правового механизмов регуляции землепользования в аграрной сфере, позволяет выявлять резервы эффективного землепользования, своевременно реагировать на отклонения и предупреждать негативные явления в контексте обеспечения роста продуктивности землепользования. У статті обґрунтована необхідність розробки єдиного документу, який би відображав державну політику у сфері ефективного землекористування, систематизував і взаємоув'язав існуючі законодавчі акти у сфері земельних відносин. В результаті дослідження розроблені основні напрямки стратегії ефективного використання сільськогосподарських земель. Стратегія державного регулювання земель сільськогосподарського користування є сукупністю організаційного, фінансово- економічного і правового механізмів регуляції землекористування в аграрній сфері, дозволяє виявляти резерви ефективного землекористування, своєчасно реагувати на відхилення і запобігати негативним явищам в контексті забезпечення зростання продуктивності землекористування. The article deals with the development of the state strategy basic directions of the effective use of agricultural lands, its general aims, tasks and implementation stages. The absence of the single program of the effective agricultural land usage and state control in this sphere puts in the forefront the necessity of single document development, which would reflect state policy in the sphere of effective land usage, systematize and connect the existent legislative acts in the sphere of the land relations. As a result of research the basic directions of development strategy of the effective agricultural land usage are offered, general aims and tasks are identified, the decision of which is to realize the state strategy. Strategy of state regulation of agricultural lands was developed. This strategy is an aggregate of organizational, financialeconomic and legal mechanisms of adjusting of land usage in an agrarian sphere. This strategy allows to expose reserves of effective land usage, to react on rejections in time and to warn the negative events in the context of providing of the land usage productivity increase. The realization of the offered initiatives will allow to put in order the sphere of the land relations considerably, to support fertility of soils and to increase the efficiency of land usage and ecologically clean production volume.